Comparison of acute kidney injury incidence after doxorubicin and cyclophosphamide chemotherapy in breast cancer patients with and without adequate oral hydration prevention - Samuel Pola Karta Sembiring; Maman Abdurahman; Raden Yohana Azhar (International Journal on Health and Medical Sciences, 2026)
Background: Breast cancer is the leading cause of cancer death among Indonesian women, and the Doxorubicin and Cyclophosphamide (AC) regimen remains one of the primary systemic therapy options. This regimen carries significant nephrotoxic effects that can trigger acute kidney injury (AKI) in 10%–32.8% of patients, potentially causing permanent kidney damage and disrupting treatment continuity. Adequate oral hydration (30 mL/kg body weight/day) is an economical, practical preventive approach that accelerates drug metabolite excretion, but its effectiveness in reducing AKI incidence in clinical practice remains unclear. Aim: To compare AKI incidence in breast cancer patients undergoing AC chemotherapy between those who received adequate oral hydration prevention and those who did not. Methods: A prospective cohort study was conducted at the Surgical Oncology Clinic of Dr. Hasan Sadikin General Hospital, Bandung, from October 2025 to February 2026. Fifty-six subjects selected by consecutive sampling were divided into a prevention group and a no-prevention group (28 each). AKI was assessed using KDIGO criteria via serum creatinine at 48 hours and 7 days post-chemotherapy, and data were analyzed with the Chi-Square test. Results: Overall AKI incidence was 25% (14 of 56 subjects): 8 cases (28.5%) in the no-prevention group versus 6 cases (21.4%) in the prevention group. The Pearson Chi-Square test yielded p = 0.469 (p > 0.05). Conclusion: Although AKI cases were numerically lower in the prevention group, adequate oral hydration did not significantly reduce AKI incidence compared with no prevention in breast cancer patients undergoing AC chemotherapy.